2013
DOI: 10.1155/2013/261523
|View full text |Cite
|
Sign up to set email alerts
|

Development and Environmental Applications of Activated Carbon Cloths

Abstract: Activated carbon cloths have received growing attention because they offer comparative advantages over the traditional powdered or granular forms of this well-known adsorbent, providing further potential uses for technological innovations in several fields. The present article provides an overview of research studies and advances concerned with the development of activated carbon cloths and their use as adsorbent in environmental applications, mostly reported in the last years. The influence of some fabrics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 182 publications
(264 reference statements)
0
41
0
1
Order By: Relevance
“…The obtained results showed that the heating rates increasing cause the pre-exponent coeffients increasing and activation energy decreasing lightly. The pronounced increase of pre -exponential factor can promote the reaction rate increasing like suggested by [4].…”
Section: Figure 6 the Effect Of Heating Rate On Carbonization Processmentioning
confidence: 82%
See 2 more Smart Citations
“…The obtained results showed that the heating rates increasing cause the pre-exponent coeffients increasing and activation energy decreasing lightly. The pronounced increase of pre -exponential factor can promote the reaction rate increasing like suggested by [4].…”
Section: Figure 6 the Effect Of Heating Rate On Carbonization Processmentioning
confidence: 82%
“…Activated carbon such as powdered or granular forms is well known owing to its widespread application in many fields as a exellent adsorbent for purification, remediation of wastewater and toxic gas generated in industry [1][2][3][4]. In the recent years the activated carbon fiber cloths have receive an increasing concern because they exhibit a comparative advantages over the traditional activated carbon, including their application in high technological inovation as use in cell therapy as a support for stem cell growth [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface chemical functionalities were measured by potentiometric titration (PT) according to the pK a distribution method based on a titration with NaOH (0.1 mol/L) using a very low incremental volume (0.01 ml) in a wide range of pH (3)(4)(5)(6)(7)(8)(9)(10)(11). The method consisted in dispersing 100 mg of ACC in 75 ml of NaNO 3 0.01 mol L À1 , previously degassed by nitrogen bubbling during 48 h. The pH of the solution was then adjusted to 3 using HCl 0.1 mol/L and titrated by NaOH.…”
Section: Textural and Chemical Surface Properties Of Accmentioning
confidence: 99%
“…Due to their microtexture and their small fiber diameters (around 10 lm), they have minimal diffusion limitation and greater adsorption rates, which makes them ideal candidates for adsorption purposes [3]. As a result, intensive research involving carbon cloths or felts has been conducted in recent years and has demonstrated the high adsorption efficiency of carbon cloths towards noxious organic pollutants.…”
Section: Introductionmentioning
confidence: 99%